Science Labs and Their Positive Impacts on Students’ Understanding of Science Concepts - Sroczynski, Eve (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2023)
Laboratory experiments are an important aspect of science students’ educational journeys. This paper demonstrates that when students perform labs in their science classes, they have an increased understanding of the associated science concepts, and they are better able to learn science as a result. Laboratory experiments give students the opportunity to enhance their discourse skills, work collaboratively with their peers, and connect science concepts to real life scenarios. Furthermore, laboratory experiments are learner-centered, and they are a tool science teachers can use that result in their students having increased understanding of abstract science concepts. All these aspects of laboratory experiments result in students having a better understanding of the content and an increased ability to learn science effectively.